Fluorinated Organic Porous Materials - Zhang, Zhenglin; Miljanić, Ognjen Š. (Organic Materials, 2019)
Fluorine is in many aspects unique among the elements, and its incorporation into organic molecules can dramatically change their physical and chemical properties. This minireview will survey the existing classes of fluorinated porous materials, with a particular focus on all-organic porous materials. We will highlight our work on the preparation and study of metal–organic frameworks and porous molecular crystals derived from extensively fluorinated rigid aromatic pyrazoles and tetrazoles. Where possible, comparisons between fluorinated and nonfluorinated materials will be made.
Keywords: fluorinated molecules; porous materials; molecular crystals; macrocycles